Simultaneous NICER and NuSTAR observations of the ultracompact x-ray binary 4u 1543-624 - Ludlam, R. M.; Jaodand, A. D.; Garcia, Javier; Degenaar, N.; Tomsick, J. A.; Cackett, E. M.; Fabian, A. C.; Gandhi, P.; Buisson, D. J. K.; Shaw, A. W.; Chakrabarty, D. (Astrophysical Journal, 2021)
We present the first joint NuSTAR and NICER observations of the ultracompact X-ray binary (UCXB) 4U 1543 -624 obtained in 2020 April. The source was at a luminosity of L0.5-50 keV = 4.9(D/7 kpc)2 × 1036 erg s-1 and showed evidence of reflected emission in the form of an O VIII line, Fe K line, and Compton hump within the spectrum. We used a full reflection model, known as XILLVERCO, that is tailored for the atypical abundances found in UCXBs, to account for the reflected emission. We tested the emission radii of the O and Fe line components and conclude that they originate from a common disk radius in the innermost region of the accretion disk (Rin . 1.07 RISCO). Assuming that the compact accretor is a neutron star (NS) and the position of the inner disk is the Alfvén radius, we placed an upper limit on the magnetic field strength to be B . 0.7(D/7 kpc) × 108 G at the poles. Given the lack of pulsations detected and position of Rin, it was likely that a boundary layer region had formed between the NS surface and inner edge of the accretion disk with an extent of 1.2 km. This implies a maximum radius of the neutron star accretor of RNS . 12.1 km when assuming a canonical NS mass of 1.4Me.
CRIS-Team Scopus Importer:2021-05-21